Body composition of starved Tufted Ducks Aythya fuligula, Pochards A. ferina and Little Grebes Tachybaptus ruficollis - Jenni-Eiermann, Susanne; Schifferli, Luc (Wildfowl, 1989)
Fresh winter mass of eleven Tufted Ducks, nine Pochards and four Little Grebes, which died in the wild most likely from starvation, are compared with data from birds in normal condition. Fat content, dry and lean dry mass were recorded by standard procedures. All starved specimens had lost 26-56% of normal fresh mass. The mean water content of the starved birds was 76-79%, lean dry mass accounted for 96-98% of dry mass, total fat made up 2.2 to 3.5% of dry mass. When estimating body condition and survival time without food intake, these values of non-metabolized tissue have to be taken into account.